2010
DOI: 10.1080/07359683.2010.519990
|View full text |Cite
|
Sign up to set email alerts
|

Looking Beyond “Affordable” Health Care: Cultural Understanding and Sensitivity—Necessities in Addressing the Health Care Disparities of the U.S. Hispanic Population

Abstract: Health disparities are pervasive in the United States; but among Hispanics, access to health care is encumbered by poverty, lack of insurance, legal status, and racial or minority status. Research has identified certain aspects of Hispanic culture, values, and traditions contributing to the nature of the Hispanic patient-doctor relationship and the quality of the health care service. Current educational efforts by nonprofit organizations, government, health professionals, and pharmaceutical manufacturers fail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…41 Using simple terminology and visual aids can assist providers in communicating. 32 When communicating with patients, providers should not appear rushed. A personalized conversation can cultivate a relationship of trust with Hispanic patients.…”
Section: Communicationmentioning
confidence: 99%
See 4 more Smart Citations
“…41 Using simple terminology and visual aids can assist providers in communicating. 32 When communicating with patients, providers should not appear rushed. A personalized conversation can cultivate a relationship of trust with Hispanic patients.…”
Section: Communicationmentioning
confidence: 99%
“…Hispanic patients are likely to state that health-care providers do not involve them in decision-making or spend enough time explaining or answering their healthcare concerns. 32 Early studies of Hispanic HF patients indicated that Hispanics were less likely than Caucasian and African Americans to receive an assessment of left ventricular ejection fraction, 33 be discharged on an angiotensin-converting enzyme inhibitor, 33 or receive complete discharge instructions at the time of hospital discharge. 34 Although the overall delivery of health care to Hispanic HF patients at hospitals has improved, 35 an examination of Medicare Hospital Cultural competency education for providers Monitor for quality outcomes and evaluate provider adherence to evidence-based practices with Hispanic patients Enhance comanagement of patient care between cardiologists and primary-care providers when patient referred from a community health center Increase Hispanic participation in National Institutes of Health-funded heart failure research trials Improve access to health insurance Use of interpreter services Use of culturally appropriate and easy to read educational material Understanding of Hispanic cultural communication behaviors B Slow-paced conversation B Avoid direct eye contact B Open and friendly nonverbal communication Present orientation time frame and using short-term treatment goals Understanding of the Hispanic respeto value system and how power distribution is imbalanced toward the provider Include family members, especially female family members, in treatment discussions, with consent of the patient Familiarity, understanding, and inclusion of Hispanic alternative therapies and the use of curanderos as appropriate Quality measures has indicated that Hispanic patients with HF are less likely to receive smoking cessation counseling and discharge instruction, especially at poorer performing hospitals.…”
Section: Lack Of Quality Health-carementioning
confidence: 99%
See 3 more Smart Citations